Antibacterial activity of silver nanoparticles: sensitivity of different Salmonella serovars - Losasso, Carmen; Belluco, Simone; Cibin, Veronica; Zavagnin, Paola; Mičetić, Ivan; Gallocchio, Federica; Zanella, Michela; Bregoli, Lisa; Biancotto, Giancarlo; Ricci, Antonia (Frontiers in Microbiology, 2014)
Salmonella spp. is one of the main causes of foodborne illnesses in humans worldwide. Consequently, great interest exists in reducing its impact on human health by lowering its prevalence in the food chain. Antimicrobial formulations in the form of nanoparticles exert bactericidal action due to their enhanced reactivity resultant from their high surface/volume ratio. Silver nanoparticles (AgNPs) are known to be highly toxic to Gram-negative and Gram-positive microorganisms, including multidrug resistant bacteria. However, few data concerning their success against different Salmonella serovars are available. Aims of the present study were to test the antimicrobial effectiveness of AgNPs, against Salmonella Enteritidis, Hadar and Senftenberg, and to investigate the causes of their different survival abilities from a molecular point of view. Results showed an immediate, time-limited and serovar-dependent reduction of bacterial viability. In the case of S. Senftenberg, the reduction in numbers was observed for up to 4 h of incubation in the presence of 200 mg/L of AgNPs; on the contrary, S. Enteritidis and S. Hadar resulted to be inhibited for up to 48 h. RT-PCR experiments demonstrated the constitutive expression of the plasmidic silver resistance determinant (SilB) by S. Senftenberg, thus suggesting the importance of a cautious use of AgNPs.